Cardiac valve prostheses, anticoagulation, and pregnancy. Issue 1 (January 1986) - Ben Ismail, M; Abid, F; Trabelsi, S; Taktak, M; Fekih, M
Abstract : The course of 76 pregnancies is reported in 51 women who became pregnant after replacement of one or more heart valves. Age at conception ranged from 17 to 39 years (mean 25). There have been 71 deliveries and five women are still pregnant at the time of writing. In the 71 pregnancies, oral anticoagulants were given during 53, heparin during five, and no anticoagulants during 13. Fetal complications consisted of 12 spontaneous abortions (eight in pregnancies in which oral anticoagulants were given, three in which heparin was given, and one in which no anticoagulants were given), of 12 premature deliveries with seven stillbirths (three on oral anticoagulants and four without anticoagulants), and there were three neonatal deaths (in all all three instances oral anticoagulants had been given during pregnancy). The maternal complications were as follows. Two women with mitral valve prostheses on heparin had thromboembolic episodes. Four women on oral anticoagulants died and 11 developed haemorrhage or systemic embolism. Two of the deaths were caused by bacterial endocarditis, one was the result of obstruction of a mitral valve prosthesis, and one was due to haemorrhage. One patient developed pulmonary oedema during delivery which rapidly resolved. Seven patients had uterine bleeding after delivery (three of them were on heparin and one was on an antiplatelet agent).